Obligations Regime of the Mining Concession (Mining rights system) - Martínez Aponte, Humberto (2014)
Mining concessions are subject to the fulfillment of liabilities by their owners based on ground for revocation, known as «expiration», as part of mining rights systems. The recent evolution of these liabilities and their focus as part of the conditions offered by the country for investment are analyzed by the author. To do this, the author conduct a review about the changes taken place in 1991 and 2008 mainly, as well as provides the elements to analyze the appropriateness of modifications or its flexibility. The tables used in the explanation constitutes a contribution, which were used by the author in conferences and due diligence for mining projects, as well as the consideration of both elements in the analysis of doctrine and real application of these concepts under the system of Peru.